2014
DOI: 10.1111/bjdp.12076
|View full text |Cite
|
Sign up to set email alerts
|

Step by step: A microgenetic study of the development of strategy choice in infancy

Abstract: To examine patterns of strategy choice and discovery during problem-solving of a novel locomotor task, 13.5- and 18-month-old infants were placed at the top of a staircase and encouraged to descend. Spontaneous stair descent strategy choices were documented step by step and trial by trial to provide a microgenetic account of problem-solving in action. Younger infants tended to begin each trial walking, were more likely to choose walking with each successive step, and were more likely to lose their balance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 96 publications
3
16
0
Order By: Relevance
“…The current results suggest that visual attention distraction and hands withholding behaviours may be strategic at this age, if we define strategic behaviour as children's intentional actions aimed at succeeding on a task. A similar meaning was ascribed to the term 'strategic behaviour' in a recent micro-genetic study examining the way in which 13-and 18-month-old infants chose to descend a novel staircase (Berger et al 2015). Following from this definition, we do not consider strategy use to be a fully conscious or metacognitive process at this age, but rather understand the term to mean the way young children approach a task or challenge with the intention of succeeding on that task or mastering that challenge.…”
Section: Discussionmentioning
confidence: 87%
“…The current results suggest that visual attention distraction and hands withholding behaviours may be strategic at this age, if we define strategic behaviour as children's intentional actions aimed at succeeding on a task. A similar meaning was ascribed to the term 'strategic behaviour' in a recent micro-genetic study examining the way in which 13-and 18-month-old infants chose to descend a novel staircase (Berger et al 2015). Following from this definition, we do not consider strategy use to be a fully conscious or metacognitive process at this age, but rather understand the term to mean the way young children approach a task or challenge with the intention of succeeding on that task or mastering that challenge.…”
Section: Discussionmentioning
confidence: 87%
“…Strikingly, in this study the mean duration of crawling bouts when infants vocalized was shorter than bouts when they did not, despite having more opportunity to do so during long bouts. Longer crawling bouts would have required more effort, particularly for novices, because maintaining an effortful posture is more taxing than reverting to a less demanding one (Berger, ; Berger, Chin, Basra, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…symbolic object use and socio-communication, on walking initiation. Findings suggest that walking initiation is linked to the probability of having attained previous symbolic communicative skills, along with a proactive reallocation of these resources [ 22 , 39 ]. This reallocation possibly serves as a mechanism for preventing over-taxing cognitive resources, thereby affording resource recruitment in order to enable earlier transition [ 40 ] to walking [ 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However little is known about changes in cognitive behaviors that precede and support the emergence of a new motor skill. A novice walker, for example, is required to plan their future movements [ 1 , 22 , 23 ], and thus their strategy choices reflect a need to invest cognitive resources (and the difficulty in doing so) [ 24 , 25 ]. Adolph and collegues [ 26 , 27 ] indicated that novice walking infants are not necessarily considering the relations between their own bodies, their skills and the relevant properties of the environment in deciding if an action such as a descent is possible or impossible [ 24 ], managing at first less challenging terraine better than more complex ones, with the latter resulting in frequent stumbing and falls [ 28 ].…”
Section: Introductionmentioning
confidence: 99%